Characteristics and prognosis in acute myocarditis and unexplained acute chest pain: a nationwide longitudinal cohort study - Elmir Omerovic; Emanuele Bobbio; Marie Björkenstam; Christian L Polte; Clara Hjalmarsson; Niklas Bergh; Entela Bollano (Open Heart)
Aims Acute myocarditis (AM) is a disease with variable prognosis, ranging from complete recovery to end-stage heart failure (HF) and death but often challenging to differentiate from unexplained acute chest pain (UCP) in the acute setting. This study examines the short-tem and long-term outcomes of AM compared with UCP, focusing on the risk of HF development.Methods We used the Swedish Web System for Enhancement of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies-registry to identify patients >16 years admitted to hospital between 1 January 1998 and 31 December 2018 with either AM or UCP. Patients were followed for outcomes including mortality, rehospitalisation and HF development over both short-term (30 days) and long-term periods. Cox proportional hazards models were used to compare the risks, adjusting for demographic and clinical-related factors.Results A total of 3792 patients with AM and 109 934 patients with UCP were included. Median follow-up time was 7.8 years (Q1, Q3; 3.4, 12.3). AM patients were younger compared with UCP patients, median age 37 years (Q1, Q3; 26, 52) vs 59 years (Q1, Q3; 49, 69) and more likely to be men (79.9% vs 51.4%, p<0.001). Comorbidity burden was less pronounced within the AM cohort. Chest pain was the most common presenting symptom in both groups. Mortality rate at 30 days (OR 3.75, 95% CI 1.9 to 7.3, p<0001) as well as long term (OR 2.0, 95% CI 1.69 to 2.39, p<0.001) were significantly higher in AM patients compared with UCP. AM patients were more likely to develop HF during follow-up (OR 2.3, 95% CI 1.81 to 2.93, p<0001).Conclusions AM is associated with worse short-term and long-term outcomes compared with UCP, including a higher risk of developing HF even after the first year.